A two-layer non-hydrostatic landslide model for tsunami generation on irregular bathymetry. 2. Numerical discretization and model validation. (April 2021) - Zhang, Cheng; Kirby, James T.; Shi, Fengyan; Ma, Gangfeng; Grilli, Stephan T.
Abstract: We describe a numerical treatment for a two-layer coupled model developed for the investigation of submarine landslides and resulting tsunami generation over irregular bathymetry. The landslide model is formulated in a Cartesian coordinate system oriented with the still water level in order to facilitate coupling between water and ground motions. Motions in the upper water layer are simulated using the 3D non-hydrostatic wave model NHWAVE. Governing equations for the lower-layer landslide are integrated over the slide thickness, and include options for choosing either Newtonian viscous or granular rheology closures. The lower layer equations retain the effects of non-hydrostatic pressure, allowing the model to simulate motions over arbitrary and locally steep bathymetry. The model equations are solved using a Runge–Kutta scheme for time integration and a Godunov-type finite volume scheme for spatial derivatives, with non-conservative terms formulated using a finite difference scheme. The resulting model is verified in comparison to two laboratory experiments involving granular slide motion, and compared to observations for a field event during the 1964 Alaska earthquake. Highlights: A two-layer model is developed for investigating tsunamis generated by landslides. The hyperbolicity of the governing equations is preserved. A well-balanced Godunov-type finite volume scheme is applied. The model is validated against laboratory and field cases with irregular bathymetry.